Central Venous Occlusion Management in Nigeria: Six Year Review of Our Experience - EDAFE, EMMANUEL AUCHI; Akpa, Maclean Rumokere (International Journal of Innovative Research in Medical Science, 2024)
Introduction: The majority of cases of stenosis or occlusion of central veins are the result of prolonged use of central catheters, neoplasms or traumas. Central vein occlusion is also common among patients with cardiac devices or chronic repeated thrombi. Central venous occlusion could be severe due to engorged neck veins, thrombosis, venous hypertension and edema of the extremities. The objective of this study is to discuss endovascular management of central venous occlusion in three Nigerian patients. Methods: This is a retrospective study of patients seen in cardiac catheterization laboratory and the Vascular C-Arm of the Bayelsa Specialist Hospital and Cardiocare Multispecialty Hospital over a period of 6 years from January 2018 to December 2023. The data were extrcated from the patients’ record and the data analyzed with SPSS version 25.0 for windos. Results: There were 31 patients in the 6-year of review. There were 19 males and 12 females. The average age of patients was 64.0 ± 9.8 years. The commonest symptoms were facial swelling, upper extremity swelling and pain. The commonest etiology was use of long indwelling venous catheters. Conclusion: Central vein stenosis and its risk factors are common in Nigeria. The endovascular treatment included use of balloon and stents.